Co-Transmission of Alpha-Synuclein and TPPP/p25 Inhibits Their Proteolytic Degradation in Human Cell Models - Lehotzky, Attila; Oláh, Judit; Fekete, János Tibor; Szénási, Tibor; Szabó, Edit; Győrffy, Balázs; Várady, György; Ovádi, Judit (Frontiers in Molecular Biosciences, 2021)
The pathological association of alpha-synuclein (SYN) and Tubulin Polymerization Promoting Protein (TPPP/p25) is a key factor in the etiology of synucleinopathies. In normal brains, the intrinsically disordered SYN and TPPP/p25 are not found together but exist separately in neurons and oligodendrocytes, respectively; in pathological states, however, they are found in both cell types due to their cell-to-cell transmission. The autophagy degradation of the accumulated/assembled SYN has been considered as a potential therapeutic target. We have shown that the hetero-association of SYN with TPPP/p25 after their uptake from the medium by human cells (which mimics cell-to-cell transmission) inhibits both their autophagy- and the ubiquitin-proteasome system-derived elimination. These results were obtained by ELISA, Western blot, FACS and immunofluorescence confocal microscopy using human recombinant proteins and living human cells; ANOVA statistical analysis confirmed that TPPP/p25 counteracts SYN degradation by hindering the autophagy maturation at the stage of LC3B-SQSTM1/p62-derived autophagosome formation and its fusion with lysosome. Recently, fragments of TPPP/p25 that bind to the interface between the two hallmark proteins have been shown to inhibit their pathological assembly. In this work, we show that the proteolytic degradation of SYN on its own is more effective than when it is complexed with TPPP/p25. The combined strategy of TPPP/p25 fragments and proteolysis may ensure prevention and/or elimination of pathological SYN assemblies.